Organization of Disaster Relief Team for Earthquake Victims (Journal of Pakistan Orthopaedic Association, 2013)
Objective: To organize disaster relief teams in every medical non medical institution irrespective of fields, government, non-government like scouts, civil defence and NCC.Design Duration: Experience of team orthopaedics unit –1, with other members of different departments of DUHS/Civil hospital Karachi and literature review of experiences of different disaster relief teams in different earthquake disaster places in the world up till 2012.Setting: A team of 31 volunteers managed more than 380 orthopaedics trauma victims of 7.9 magnitude earthquake in Pakistan.Methodology: With collaboration of Higher Education Commission and Higher Government Authority Islamabad established a field base camp tent hospital at Battagram replacing District Head Quarter Hospital District Battagram, N.W.F.P.Experiences of different disaster teams, data collected through literature published in national and international recognized journals.Results:-Out of 380 patients of different age group male were 170 (44.26%) and female 210(55.76%). 362 patients were managed conservatively and surgical procedures done upon 14 (3.68%) and 4 (1.05%) cases referred to major hospital.Conclusions: Disaster Relief Team doesn’t mean a team of medical expertise, staff nurse and paramedical staff because the place where we are going to give medical facilities; that is devoid of all necessities of life for human being. The team should consist of doctors, paramedical staff (O.T. technician, male attendant, staff nurse, sweeper, cook, plumber cum electrician, etc.Medical and non medical organization should educate and train to staff for such emergency situations just like civil defence, NCC and. scouts. Especially they would be trained of Primary Trauma Care Provider, Basic Life Support and C.P.R